Association Between Extracellular Superoxide Dismutase Activity and 1-Year All-Cause Mortality in Patients With Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Prospective Cohort Study - Li, Haiqing; Hong, Wei; Zeng, Zixiong; Gong, Shan; Wu, Fan; Wang, Zihui; Tian, Heshen; Cheng, Juan; Sun, Ruiting; Gao, Mi; Liang, Chunxiao; Cao, Weitao; et al. (Frontiers in Medicine, 2022)
Background and objectives: Accumulating evidence suggests that oxidative stress is involved in the development of chronic obstructive pulmonary disease (COPD) and its progression. Levels of extracellular superoxide dismutase (ecSOD) activity, the only extracellular enzyme eliminating superoxide radicals, have been reported to decline in acute exacerbations of COPD (AECOPD). However, the association between serum ecSOD activity and 1-year all-cause mortality in AECOPD patients remains unclear. The objective of our study was to explore the usefulness of ecSOD activity on admission in AECOPD as an objective predictor for 1-year all-cause mortality. Methods: We measured serum ecSOD activity in AECOPD patients on admission in a prospective cohort study. We also recorded their laboratory and clinical data. Multivariate Cox regression was used to analyze the association between ecSOD activity and the risk of 1-year all-cause mortality. Restricted cubic spline curves were used to visualize the relationship between ecSOD activity and the hazard ratio of 1-year all-cause mortality. Results: A total of 367 patients were followed up for 1 year, and 29 patients died during a 1-year follow-up period. Compared with survivors, the non-survivors were older (79.52±8.39 vs. 74.38±9.34 years old, p=0.004) and had increased levels of tobacco consumption (47.07±41.67 vs. 33.83±31.79 pack-years, p=0.037). Having an ecSOD activity ≤98.8 U/mL was an independent risk factor of 1-year all-cause mortality after adjustment for baseline differences, clinical variables and comorbidities (hazard ratio=5.51, 95% confidence interval [CI]: 2.35–12.95, p<0.001). Conclusion: Lower serum ecSOD activity was a strong and independent predictor of 1-year all-cause mortality in AECOPD patients.